Broadband-gap perovskite solar cell and preparation method thereof
By introducing 4,5-dicyanoimidazole as an additive in perovskite solar cells, a strong coordination structure with iodine ions is formed, which solves the problem of photophase segregation and significantly improves the stability and efficiency of the battery.
Patent Information
- Application Number
- CN202411843784.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-14
- Publication Date
- 2025-03-21
AI Technical Summary
During the process of adjusting the band gap, existing perovskite solar cells are prone to photophase segregation, which affects the stability and efficiency of the battery.
During the preparation of perovskite solar cells, 4,5-dicyanoimidazole is introduced as an additive to form a strong coordination structure with iodine ions, inhibiting the precipitation of iodine, thereby improving the stability of the battery.
It effectively inhibits the precipitation of iodine, improves the stability and photoelectric conversion efficiency of wide-bandgap perovskite solar cells, and extends the service life of the battery.
Smart Images

Figure CN119677376A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy, and in particular relates to a wide bandgap perovskite solar cell and a preparation method thereof. Background Art
[0002] Perovskite materials have shown great application potential in the field of solar cells due to their excellent photoelectric conversion efficiency and adjustable bandgap characteristics. The artificial synthesis characteristics of perovskite materials allow researchers to precisely control the bandgap by adjusting the material ratio. The bandgap is the lowest energy that a semiconductor can absorb, which determines the material's absorption range and efficiency of photons. This characteristic of perovskite materials enables it to be combined with a variety of inorganic absorption layers to prepare high-efficiency photovoltaic devices, such as crystalline silicon / perovskite stacked solar cells, translucent / thermochromic cells, etc. In addition, perovskite materials also have the characteristics of changeable colors, light weight, and good flexibility, which give them incomparable advantages in fields such as photovoltaic building integration (BIPV).
[0003] In order to further optimize the performance of perovskite solar cells, researchers have explored a variety of methods to adjust the band gap of perovskite materials. Doping is an effective strategy. By introducing other elements into perovskite materials, their electronic structure and energy level distribution can be changed, thereby affecting the band gap width. For example, the introduction of bromide can effectively adjust the band gap of perovskite to meet the requirements of the spectral response range for specific applications. Alloying is another feasible strategy. By alloying with other materials with similar structures, new perovskite structures can be formed, thereby changing their band gaps. In addition, the band gap of perovskite materials can also be adjusted by changing the preparation conditions and post-processing methods, such as adjusting parameters such as temperature, pressure and time during the preparation process, or performing post-processing steps such as annealing and surface treatment. These methods provide a broader space for the application of perovskite materials in the optoelectronic field.
[0004] Although doping strategies such as adding bromide can effectively adjust the band gap of perovskite materials and improve the photoelectric conversion efficiency of solar cells, it also brings about the problem of photoinduced phase segregation. Photoinduced phase segregation refers to the phase separation phenomenon of perovskite materials under light, which seriously affects the photovoltaic performance of mixed halide perovskite materials. The specific cause of photoinduced phase segregation has not yet been fully clarified, but it is generally believed to be related to factors such as the local electric field generated by defects at grain boundaries, the release of lattice distortion stress, and the change in material free energy caused by light. Phase segregation not only causes structural destruction and performance degradation of perovskite materials, but also has an adverse effect on the long-term operation stability of solar cells. Therefore, how to effectively suppress the photoinduced phase segregation phenomenon while adjusting the band gap of perovskite materials has become a hot topic and difficulty in current research. In order to overcome this challenge, researchers are actively exploring new doping strategies, optimizing material preparation processes, and developing new packaging materials to improve the stability and efficiency of perovskite solar cells. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a wide bandgap perovskite solar cell and a preparation method thereof, so as to solve the technical problem of how to effectively inhibit iodine precipitation and thus improve the stability of the wide bandgap perovskite solar cell.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a method for preparing a wide bandgap perovskite solar cell, comprising the following steps: 1) NiO x The solution was spin-coated on the pretreated substrate and dried to obtain NiO x hole transport layer; 2) FAI, CsI, PbBr2 and PbI2 are mixed and dissolved in a mixed solution of DMF and DMSO, and then an additive is added to obtain a perovskite precursor solution; the perovskite precursor solution is coated on the NiO obtained in step 1) by a two-step spin coating method. x On the hole transport layer, after annealing, a perovskite layer is obtained; 3) Sequentially prepare the electron transport layer and the electrode layer to obtain a wide bandgap perovskite solar cell; In step 2), the additive is 4,5-dicyanoimidazole.
[0007] Preferably, in step 1), NiO x The concentration of the solution is 3-15 mg / ml; the substrate is ITO glass or FTO glass; the pretreatment conditions are: ultrasonic cleaning with water, alcohol and isopropanol for 10 minutes in sequence, and then drying in a nitrogen atmosphere; the spin coating rate is 3000-5000 rpm; and the spin coating time is 15-30 seconds.
[0008] Preferably, in step 1), the drying temperature is 80-150° C., and the drying time is 5-30 min.
[0009] Preferably, in step 2), FAI, CsI, PbBr2 and PbI2 are prepared according to the ratio of Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3 is weighed; in the mixed solution of DMF and DMSO, the volume ratio of DMF and DMSO is 4: (0~1).
[0010] Preferably, in step 2), the amount of the additive added is 0.1-1 mol % of the perovskite precursor solution.
[0011] Preferably, in step 2), the specific steps of the two-step spin coating method include: firstly, spin coating the perovskite precursor solution at a rotation speed of 1000-3000 rpm for 5-15 s; then, increasing the rotation speed to 5000 rpm and spin coating for 30-50 s, and adding an anti-solvent at 30-40 s; the anti-solvent is ethyl acetate, and the amount of the anti-solvent added is 2-5 times the volume of the perovskite precursor solution.
[0012] Preferably, in step 2), the annealing treatment conditions are: annealing at 100-150° C. for 20-40 min.
[0013] Preferably, the preparation method of the electron transport layer comprises: evaporating C60 on the perovskite layer to obtain electron transport; the thickness of C60 is 20-50 nm, and the evaporation rate is 0.1-0.5 Å s -1 .
[0014] Preferably, the preparation method of the electrode layer comprises: evaporating a gold electrode on the electron transport layer to obtain the electrode layer; the thickness of the gold electrode is 60-120 nm, and the evaporation rate is 1-5 Å s -1 .
[0015] The invention also discloses a wide bandgap perovskite solar cell, which is prepared by adopting the preparation method of the wide bandgap perovskite solar cell.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a method for preparing a wide bandgap perovskite solar cell, wherein NiO is prepared by a spin coating process. x The solution was evenly coated on the pretreated substrate and dried to form a dense NiO x Hole transport layer. NiO xAs an efficient hole transport material, it can effectively transfer photogenerated holes from the perovskite layer to the electrode, thereby improving the photoelectric conversion efficiency of the battery. x The layer can also block the backflow of electrons and protect the perovskite layer from erosion by the external environment, which is beneficial to the stability and durability of the battery. By accurately weighing each component and dissolving it in a mixed solution of DMF and DMSO in a specific ratio, a uniform and transparent perovskite precursor solution is formed. The mixed solvent of DMF and DMSO can dissolve these components well, ensuring the uniformity and stability of the precursor solution. The introduction of the additive 4,5-dicyanoimidazole can form a strong coordination structure with the iodine ions in the precursor solution, effectively inhibiting the precipitation of iodine, thereby improving the stability of the battery. In addition, the additive may also have a positive effect on the crystallization process of the perovskite layer, further optimizing the performance of the battery. The two-step spin coating method can more accurately control the thickness and uniformity of the perovskite layer to ensure the efficient operation of the battery. Annealing is a key step in the formation of the perovskite layer, which can crystallize the solute in the precursor solution to form a high-quality perovskite layer. By optimizing the annealing conditions, the crystallization quality and performance of the perovskite layer can be further improved, thereby improving the photoelectric conversion efficiency and stability of the battery. The preparation of the electron transport layer and the electrode layer is a key step in completing solar cells. The efficient electron transport layer ensures the rapid transmission and collection of electrons in the battery, while the metal electrode forms a good electrical contact and current collection. The preparation quality and process of these two layers have an important impact on the performance and stability of the battery. By optimizing the preparation process and material selection, the photoelectric conversion efficiency and long-term stability of the battery can be further improved.
[0017] The wide band gap perovskite solar cell prepared by the method for preparing the wide band gap perovskite solar cell disclosed in the present invention adopts high quality NiO x As a hole transport layer, its excellent hole transport performance ensures that photogenerated holes can be efficiently transported from the perovskite layer to the electrode, reducing the loss of holes during the transmission process. The wide-bandgap perovskite layer (bandgap of 1.65eV) can more effectively absorb and utilize a wide spectral range of sunlight, especially light in the long wavelength region, thereby improving the utilization rate of sunlight by the battery. The introduction of the additive 4,5-dicyanoimidazole stabilizes the perovskite structure by forming a strong coordination structure with the iodine ions in the precursor solution, reduces non-radiative recombination caused by iodine ion migration, and further improves the photoelectric conversion efficiency. As an additive, 4,5-dicyanoimidazole effectively inhibits the precipitation and migration of iodine, significantly improving the stability of the battery under environmental conditions such as light, humidity and temperature changes. Dense NiO xThe hole transport layer not only plays the role of transporting holes, but also serves as a protective layer to prevent the external environment from corroding the perovskite layer, thereby extending the service life of the battery. The preparation of an efficient electron transport layer and metal electrodes ensures the rapid transmission and collection of electrons in the battery, and reduces the battery performance degradation caused by electron accumulation. The wide bandgap perovskite solar cell prepared by the present invention has efficient and stable photoelectric conversion performance, and can be widely used in solar power generation, photovoltaic building integration, portable power supplies and other fields. Especially in application scenarios with high requirements for battery performance and stability, such as aerospace, military equipment, telecommunications, etc., the battery prepared by the present invention will show greater application potential and advantages. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a schematic diagram of the structural formula of 4,5-dicyanoimidazole disclosed in the present invention; Figure 2 The cell efficiency attenuation curve diagram of the wide bandgap perovskite solar cell disclosed in Example 1 of the present invention and the perovskite solar cell prepared in Comparative Example 1 is shown. DETAILED DESCRIPTION
[0019] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0020] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0021] The present invention is further described in detail below in conjunction with the accompanying drawings: The invention provides a method for preparing a wide bandgap perovskite solar cell, which provides an additive 4,5-dicyanoimidazole strategy. The additive 4,5-dicyanoimidazole forms a strong coordination structure with iodide ions, which can effectively inhibit the precipitation of iodine, thereby improving the stability of the wide bandgap solar cell.
[0022] The present invention discloses a method for preparing a wide bandgap perovskite solar cell, comprising the following steps: 1) Preparation of NiO x Nanoparticle hole transport layer Material preparation: First, select high-quality NiO x Nanoparticles are used as raw materials to ensure that their purity and particle size meet the preparation requirements.
[0023] Solution configuration: NiO x The nanoparticles were dissolved in deionized water at a concentration of 3-15 mg / ml and stirred thoroughly with a magnetic stirrer to ensure that the particles were evenly dispersed to form a stable NiO x Nanoparticles in aqueous solution.
[0024] Spin coating process: Spin the prepared NiO x The nanoparticle aqueous solution is dropped onto a substrate (ITO glass or FTO glass) that has been pretreated by ultrasonic cleaning with water, alcohol and isopropanol for 10 minutes and drying under a nitrogen atmosphere, and then spin-coated at a speed of 3000-5000 rpm for 15-30 seconds using a spin coater to evenly cover the surface of the substrate with the solution.
[0025] Drying treatment: Place the spin-coated sample in an oven at 80-150°C for 5-30 minutes to remove the solvent and form a dense NiO x Hole transport layer.
[0026] 2) Preparation of perovskite layer with a band gap of 1.65 eV (Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3) Precursor solution configuration: According to the stoichiometric ratio, accurately weigh FAI, CsI, PbBr2 and PbI2, and dissolve them in a mixed solution of DMF and DMSO (volume ratio is 4: (0~1)), add 4,5-dicyanoimidazole (DICI) with a molar ratio of 0.1~1mol% as an additive to form a 1.4M perovskite precursor solution. This step requires ensuring that each component is fully dissolved to form a uniform and transparent solution. The addition of DICI will form a strong coordination structure with iodide ions, effectively inhibiting the precipitation of iodine and improving the stability of the battery.
[0027] Preparation of perovskite layer: The prepared perovskite precursor solution is evenly coated on the NiO by a two-step spin coating method. x On the hole transport layer, the perovskite precursor solution was first spin-coated at a speed of 1000-3000 rpm for 5-15 seconds; then the speed was increased to 5000 rpm for 30-50 seconds, and at 30-40 seconds, ethyl acetate, an anti-solvent, was added in an amount of 2-5 times the volume of the perovskite precursor solution, and then annealed at 100-150°C for 20-40 minutes to allow the precursor solution to crystallize into a perovskite layer (Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3). Annealing conditions need to be optimized according to specific experimental conditions to ensure the crystallization quality and performance of the perovskite layer.
[0028] 3) Preparation of electron transport layer Preparation of electron transport layer: Electron transport is obtained by evaporating C60 on the perovskite layer; the thickness of C60 is 20~50nm, and the evaporation rate is 0.1~0.5 Å s -1 This is achieved through methods such as spin coating, spray coating or chemical vapor deposition to ensure efficient transmission of electrons in the battery.
[0029] 4) Preparation of electrode layer Electrode layer preparation: The electrode layer is obtained by evaporating a gold electrode on the electron transport layer; the thickness of the gold electrode is 60~120nm, and the evaporation rate is 1~5 Å s -1 A metal electrode is prepared on the electron transport layer by thermal evaporation, sputtering or electrochemical deposition to form a good electrical contact and current collection.
[0030] The present invention provides an additive 4,5-dicyanoimidazole (DICI) strategy. The strong coordination between DICI and iodide ions effectively inhibits the precipitation of iodine, thereby significantly improving the stability of wide-bandgap solar cells. In addition, the introduction of DICI may also have a positive impact on the crystallization process of the perovskite layer, further optimizing the performance of the battery. The preparation method of the wide-bandgap perovskite solar cell proposed in the present invention is innovative, feasible and practical. By optimizing the preparation process and the use of additives, it is expected to prepare efficient and stable solar cells, providing new technical support for the development of the field of solar energy utilization.
[0031] Example 1 A method for preparing a wide bandgap perovskite solar cell comprises the following steps: 1) Preparation of NiO x Nanoparticle hole transport layer First, NiO xThe nanoparticles were dissolved in deionized water at a concentration of 5 mg / ml and stirred thoroughly with a magnetic stirrer to ensure that the particles were evenly dispersed to form a stable NiO x Nanoparticle aqueous solution. x The nanoparticle aqueous solution was added to the ITO glass that was ultrasonically cleaned with water, alcohol and isopropanol for 10 minutes, dried in a nitrogen atmosphere, and then spin-coated at 4000 rpm for 20 seconds to evenly cover the surface of the substrate. Subsequently, it was placed in an oven at 120°C for 10 minutes to remove the solvent and form a dense NiO x Hole transport layer.
[0032] 2) Preparation of perovskite layer with a band gap of 1.65 eV (Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3) According to the stoichiometric ratio, FAI, CsI, PbBr2 and PbI2 are accurately weighed and dissolved in a mixed solution of DMF and DMSO (volume ratio of 4:1), and DICI with a molar ratio of 0.5 mol% is added as an additive to form a 1.4M perovskite precursor solution. This step requires ensuring that each component is fully dissolved to form a uniform and transparent solution. The addition of DICI will form a strong coordination structure with iodide ions, effectively inhibiting the precipitation of iodine and improving the stability of the battery. The prepared perovskite precursor solution is evenly coated on the NiO by a two-step spin coating method. x On the hole transport layer, the perovskite precursor solution was first spin-coated at 2000 rpm for 10 seconds; then the speed was increased to 5000 rpm for 40 seconds. At 35 seconds, ethyl acetate, an anti-solvent with a volume three times that of the perovskite precursor solution, was added, and then annealed at 100 ° C for 30 minutes to allow the precursor solution to crystallize into a perovskite layer with a band gap of 1.65 eV (Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3).
[0033] 3) Preparation of electron transport layer Electron transport was obtained by evaporating C60 on the perovskite layer; the thickness of C60 was 30 nm and the evaporation rate was 0.3 Ås -1 . This is achieved by spin coating to ensure efficient transport of electrons in the battery.
[0034] 4) Preparation of electrode layer The electrode layer was obtained by evaporating a gold electrode on the electron transport layer; the thickness of the gold electrode was 100 nm and the evaporation rate was 2 Å s -1A layer of metal electrode is prepared on the electron transport layer by thermal evaporation to form a good electrical contact and current collection.
[0035] Example 2 A method for preparing a wide bandgap perovskite solar cell comprises the following steps: 1) Preparation of NiO x Nanoparticle hole transport layer First, NiO x The nanoparticles were dissolved in deionized water at a concentration of 3 mg / ml and stirred thoroughly with a magnetic stirrer to ensure that the particles were evenly dispersed to form a stable NiO x Nanoparticle aqueous solution. x The nanoparticle aqueous solution was added to the FTO glass that was ultrasonically cleaned with water, alcohol and isopropanol for 10 minutes, dried in a nitrogen atmosphere, and then spun at 3000 rpm for 15 seconds using a spin coater to evenly cover the surface of the substrate. Subsequently, it was placed in an oven at 80°C for 5 minutes to remove the solvent and form a dense NiO x Hole transport layer.
[0036] 2) Preparation of perovskite layer with a band gap of 1.65 eV (Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3) According to the stoichiometric ratio, FAI, CsI, PbBr2 and PbI2 were accurately weighed and dissolved in DMF solution, and DICI with a molar ratio of 0.1 mol% was added as an additive to form a 1.4M perovskite precursor solution. This step needs to ensure that each component is fully dissolved to form a uniform and transparent solution. The addition of DICI will form a strong coordination structure with iodide ions, effectively inhibiting the precipitation of iodine and improving the stability of the battery. The prepared perovskite precursor solution is evenly coated on the NiO by a two-step spin coating method. x On the hole transport layer, the perovskite precursor solution was first spin-coated at 1000 rpm for 5 seconds; then the speed was increased to 5000 rpm for 30 seconds. At the 30th second, the anti-solvent ethyl acetate with a volume twice that of the perovskite precursor solution was added, and then annealed at 120°C for 20 minutes to allow the precursor solution to crystallize into a perovskite layer with a band gap of 1.65 eV (Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3).
[0037] 3) Preparation of electron transport layer Electron transport was obtained by evaporating C60 on the perovskite layer; the thickness of C60 was 20 nm and the evaporation rate was 0.1 Ås -1 . This is achieved by spraying to ensure efficient transmission of electrons in the battery.
[0038] 4) Preparation of electrode layer The electrode layer was obtained by evaporating a gold electrode on the electron transport layer; the thickness of the gold electrode was 60 nm and the evaporation rate was 1 Å s -1 A metal electrode is prepared on the electron transport layer by sputtering to form a good electrical contact and current collection.
[0039] Example 3 A method for preparing a wide bandgap perovskite solar cell comprises the following steps: 1) Preparation of NiO x Nanoparticle hole transport layer First, NiO x The nanoparticles were dissolved in deionized water at a concentration of 10 mg / ml and stirred thoroughly with a magnetic stirrer to ensure that the particles were evenly dispersed to form a stable NiO x Nanoparticle aqueous solution. x The nanoparticle aqueous solution was added to the ITO glass that had been ultrasonically cleaned with water, alcohol and isopropanol for 10 minutes, dried in a nitrogen atmosphere, and then spin-coated at 3500 rpm for 25 seconds to evenly cover the surface of the substrate. Subsequently, it was placed in an oven at 100°C for 20 minutes to remove the solvent and form a dense NiO x Hole transport layer.
[0040] 2) Preparation of perovskite layer with a band gap of 1.65 eV (Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3) According to the stoichiometric ratio, FAI, CsI, PbBr2 and PbI2 were accurately weighed and dissolved in a mixed solution of DMF and DMSO (volume ratio of 4:1), and DICI with a molar ratio of 0.8 mol% was added as an additive to form a 1.4 M perovskite precursor solution. This step requires ensuring that each component is fully dissolved to form a uniform and transparent solution. The addition of DICI will form a strong coordination structure with iodide ions, effectively inhibiting the precipitation of iodine and improving the stability of the battery. The prepared perovskite precursor solution is evenly coated on the NiO by a two-step spin coating method. xOn the hole transport layer, the perovskite precursor solution was first spin-coated at 1500 rpm for 12 seconds; then the speed was increased to 5000 rpm for 35 seconds. At the 32nd second, ethyl acetate, an anti-solvent with a volume of 4 times that of the perovskite precursor solution, was added, and then annealed at 130°C for 25 minutes to allow the precursor solution to crystallize into a perovskite layer with a band gap of 1.65 eV (Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3).
[0041] 3) Preparation of electron transport layer Electron transport was obtained by evaporating C60 on the perovskite layer; the thickness of C60 was 40nm and the evaporation rate was 0.2Ås -1 . This is achieved through chemical vapor deposition to ensure efficient transport of electrons in the battery.
[0042] 4) Preparation of electrode layer The electrode layer was obtained by evaporating a gold electrode on the electron transport layer; the thickness of the gold electrode was 80 nm and the evaporation rate was 3 Å s -1 A metal electrode is prepared on the electron transport layer by electrochemical deposition to form a good electrical contact and current collection.
[0043] Example 4 A method for preparing a wide bandgap perovskite solar cell comprises the following steps: 1) Preparation of NiO x Nanoparticle hole transport layer First, NiO x The nanoparticles were dissolved in deionized water at a concentration of 15 mg / ml and stirred thoroughly with a magnetic stirrer to ensure that the particles were evenly dispersed to form a stable NiO x Nanoparticle aqueous solution. x The nanoparticle aqueous solution was added to the ITO glass that was ultrasonically cleaned with water, alcohol and isopropanol for 10 minutes, dried in a nitrogen atmosphere, and then spin-coated at 5000 rpm for 30 seconds to evenly cover the surface of the substrate. Subsequently, it was placed in an oven at 150°C for 30 minutes to remove the solvent and form a dense NiO x Hole transport layer.
[0044] 2) Preparation of perovskite layer with a band gap of 1.65 eV (Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3) According to the stoichiometric ratio, FAI, CsI, PbBr2 and PbI2 are accurately weighed and dissolved in a mixed solution of DMF and DMSO (volume ratio of 4:1), and DICI with a molar ratio of 1 mol% is added as an additive to form a 1.4M perovskite precursor solution. This step requires ensuring that each component is fully dissolved to form a uniform and transparent solution. The addition of DICI will form a strong coordination structure with iodide ions, effectively inhibiting the precipitation of iodine and improving the stability of the battery. The prepared perovskite precursor solution is evenly coated on the NiO by a two-step spin coating method. x On the hole transport layer, the perovskite precursor solution was first spin-coated at 3000 rpm for 15 seconds; then the speed was increased to 5000 rpm for 50 seconds. At the 40th second, ethyl acetate, an anti-solvent with a volume of 5 times that of the perovskite precursor solution, was added, and then annealed at 150°C for 40 minutes to allow the precursor solution to crystallize into a perovskite layer with a band gap of 1.65 eV (Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3).
[0045] 3) Preparation of electron transport layer Electron transport was obtained by evaporating C60 on the perovskite layer; the thickness of C60 was 50 nm and the evaporation rate was 0.5 Ås -1 . This is achieved by spin coating to ensure efficient transport of electrons in the battery.
[0046] 4) Preparation of electrode layer The electrode layer was obtained by evaporating a gold electrode on the electron transport layer; the thickness of the gold electrode was 120 nm and the evaporation rate was 5 Å s -1 A layer of metal electrode is prepared on the electron transport layer by thermal evaporation to form a good electrical contact and current collection.
[0047] Comparative Example 1 A method for preparing a perovskite solar cell comprises the following steps: 1) Preparation of NiO x Nanoparticle hole transport layer First, NiO x The nanoparticles were dissolved in deionized water at a concentration of 5 mg / ml and stirred thoroughly with a magnetic stirrer to ensure that the particles were evenly dispersed to form a stable NiO x Nanoparticle aqueous solution. xThe nanoparticle aqueous solution was added to the ITO glass that was ultrasonically cleaned with water, alcohol and isopropanol for 10 minutes, dried in a nitrogen atmosphere, and then spin-coated at 4000 rpm for 20 seconds to evenly cover the surface of the substrate. Subsequently, it was placed in an oven at 120°C for 10 minutes to remove the solvent and form a dense NiO x Hole transport layer.
[0048] 2) Preparation of perovskite layer (Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3) According to the stoichiometric ratio, accurately weigh FAI, CsI, PbBr2 and PbI2, and dissolve them in a mixed solution of DMF and DMSO (volume ratio of 4:1) to form a 1.4M perovskite precursor solution. This step must ensure that each component is fully dissolved to form a uniform and transparent solution. The addition of DICI will form a strong coordination structure with iodine ions, effectively inhibiting the precipitation of iodine and improving the stability of the battery. The prepared perovskite precursor solution is evenly coated on the NiO by a two-step spin coating method. x On the hole transport layer, the perovskite precursor solution was first spin-coated at 2000 rpm for 10 seconds; then the speed was increased to 5000 rpm for 40 seconds. At 35 seconds, ethyl acetate, an anti-solvent with a volume three times that of the perovskite precursor solution, was added, and then annealed at 100 ° C for 30 minutes to allow the precursor solution to crystallize into a perovskite layer with a band gap of 1.65 eV (Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3).
[0049] 3) Preparation of electron transport layer Electron transport was obtained by evaporating C60 on the perovskite layer; the thickness of C60 was 30 nm and the evaporation rate was 0.3 Ås -1 . This is achieved by spin coating to ensure efficient transport of electrons in the battery.
[0050] 4) Preparation of electrode layer The electrode layer was obtained by evaporating a gold electrode on the electron transport layer; the thickness of the gold electrode was 100 nm and the evaporation rate was 2 Å s -1 A layer of metal electrode is prepared on the electron transport layer by thermal evaporation to form a good electrical contact and current collection.
[0051] The difference between Comparative Example 1 and Example 1 is that the additive 4,5-dicyanoimidazole is not added.
[0052] See also Figure 1The schematic diagram of the structural formula of 4,5-dicyanoimidazole disclosed in the present invention is shown. As an organic compound with a unique molecular structure, 4,5-dicyanoimidazole (DICI) has shown significant application potential in the field of wide bandgap solar cells. The five-membered ring structure in its molecule connects nitrogen atoms and hydrogen atoms and carries two cyano functional groups. These characteristics together give DICI excellent coordination ability. When combined with iodide ions, the coordination ability of DICI is fully exerted. Iodide ions play an important role in battery electrolytes, but their precipitation can lead to unstable battery performance and decreased efficiency. The nitrogen atoms in the DICI molecule can form strong coordination bonds with iodine ions, effectively inhibiting the precipitation of iodine, thereby stabilizing the electrolyte and preventing the formation and deposition of iodine. From an electrochemical point of view, the introduction of DICI not only improves the stability of the battery, but also optimizes its electrochemical performance. It reduces the overpotential of the iodine reduction reaction and increases the fill factor and open circuit voltage of the battery. The improvement of these parameters is crucial to improving the overall performance of solar cells. In addition, the coordination effect of DICI can also adjust the redox potential of iodine-based electrolytes, further optimizing the energy conversion efficiency of the battery. In the field of materials science, the introduction of DICI can also improve the stability of perovskite materials and prevent their degradation under humid and light conditions. The introduction of DICI into perovskite materials by chemical doping or surface modification can significantly improve the durability and moisture resistance of the materials, thereby extending the service life of solar cells. The application of the coordination effect of 4,5-dicyanoimidazole with iodide ions in wide-bandgap solar cells not only improves the stability of the battery, but also optimizes its electrochemical performance and material stability. This strategy provides a new research direction and application prospect for the development of efficient and stable perovskite solar cells, and demonstrates the broad application potential of DICI in the field of materials science.
[0053] Figure 2 The graph is a cell efficiency decay curve of the wide bandgap perovskite solar cell disclosed in Example 1 of the present invention and the perovskite solar cell prepared in Comparative Example 1; it can be seen from the graph that the wide bandgap perovskite solar cell with the addition of 4,5-dicyanoimidazole exhibits excellent stability, with an efficiency decay of about 3% after 500 hours of photothermal coupling, while the efficiency decay of the perovskite solar cell prepared in Comparative Example 1 without the addition of 4,5-dicyanoimidazole reaches about 7%.
[0054] The present invention selects high-quality NiO x Nanoparticles ensure the quality of the basic materials of the hole transport layer, providing a guarantee for the efficient and stable operation of the battery. x The nanoparticles are dissolved in deionized water at a specific concentration to form a stable aqueous solution, which is beneficial to the subsequent spin coating process and ensures the uniformity and density of the hole transport layer. Through precise spin coating parameters (such as speed and time), NiOx The uniform coverage of the solution on the substrate lays the foundation for the formation of a high-quality hole transport layer. The appropriate drying temperature and time not only remove the solvent, but also promote the NiO x The close arrangement of the nanoparticles forms a dense hole transport layer, which is beneficial to the effective transport of holes and the stable operation of the battery. By accurately weighing each component and dissolving it in a mixed solution of DMF and DMSO in a specific proportion, a uniform and transparent perovskite precursor solution is formed, which provides a basis for the preparation of high-quality perovskite layers. Adding 4,5-dicyanoimidazole (DICI) as an additive to the precursor solution is a major innovation of the present invention. DICI forms a strong coordination structure with iodide ions, which effectively inhibits the precipitation of iodine and significantly improves the stability of the battery. At the same time, the introduction of DICI may also have a positive effect on the crystallization process of the perovskite layer, further optimizing the performance of the battery. The precursor solution is evenly coated on the NiO by spin coating or scraping. x A perovskite layer with a band gap of 1.65 eV is formed on the hole transport layer after annealing. This step not only achieves the precise preparation of the perovskite layer, but also optimizes the crystallization quality and performance of the perovskite layer through annealing, providing a key guarantee for the efficient operation of the battery. An efficient electron transport layer is prepared on the perovskite layer to ensure the effective transmission of electrons in the battery. This step is crucial to improving the photoelectric conversion efficiency and stability of the battery. A layer of metal electrode is prepared on the electron transport layer to form a good electrical contact and current collection. The selection and preparation process of the metal electrode have an important influence on the conductivity and long-term stability of the battery.
[0055] In summary, the method for preparing a wide bandgap perovskite solar cell disclosed in the present invention achieves efficient and stable operation of the cell through precise material preparation, solution configuration, spin coating process, drying treatment, precursor solution configuration, additive introduction, perovskite layer preparation, and preparation of electron transport layer and electrode layer. In particular, the introduction of the additive DICI significantly improves the stability of the cell, providing new ideas and technical support for the development of perovskite solar cells.
[0056] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a wide bandgap perovskite solar cell, characterized in that: The following steps are involved: 1) NiO x The solution was spin-coated on the pretreated substrate and dried to obtain NiO x hole transport layer; 2) FAI, CsI, PbBr2 and PbI2 are mixed and dissolved in a mixed solution of DMF and DMSO, and then an additive is added to obtain a perovskite precursor solution; the perovskite precursor solution is coated on the NiO obtained in step 1) by a two-step spin coating method. x On the hole transport layer, after annealing, a perovskite layer is obtained; 3) Sequentially prepare the electron transport layer and the electrode layer to obtain a wide bandgap perovskite solar cell; In step 2), the additive is 4,5-dicyanoimidazole.
2. The method for preparing a wide bandgap perovskite solar cell according to claim 1, characterized in that: In step 1), the NiO x The concentration of the solution is 3-15 mg / ml; the substrate is ITO glass or FTO glass; the pretreatment conditions are: ultrasonic cleaning with water, alcohol and isopropanol for 10 minutes in sequence, and then drying in a nitrogen atmosphere; the spin coating rate is 3000-5000 rpm; and the spin coating time is 15-30 seconds.
3. The method for preparing a wide bandgap perovskite solar cell according to claim 1, characterized in that: In step 1), the drying temperature is 80-150° C., and the drying time is 5-30 min.
4. The method for preparing a wide bandgap perovskite solar cell according to claim 1, characterized in that: In step 2), the FAI, CsI, PbBr2 and PbI2 are prepared according to the Cs 0.25 FA 0.75 Pb(I 0.85 Br 0.15 )3 is weighed according to the stoichiometric ratio; in the mixed solution of DMF and DMSO, the volume ratio of DMF and DMSO is 4: (0~1).
5. The method for preparing a wide bandgap perovskite solar cell according to claim 1, characterized in that: In step 2), the amount of the additive added is 0.1-1 mol% of the perovskite precursor solution.
6. The method for preparing a wide bandgap perovskite solar cell according to claim 1, characterized in that: In step 2), the specific steps of the two-step spin coating method include: firstly spin coating the perovskite precursor solution at a rotation speed of 1000-3000 rpm for 5-15 seconds; then increasing the rotation speed to 5000 rpm and spin coating for 30-50 seconds, and adding an anti-solvent at 30-40 seconds; the anti-solvent is ethyl acetate, and the amount of the anti-solvent added is 2-5 times the volume of the perovskite precursor solution.
7. The method for preparing a wide bandgap perovskite solar cell according to claim 1, characterized in that: In step 2), the annealing treatment conditions are: annealing at 100-150° C. for 20-40 min.
8. The method for preparing a wide bandgap perovskite solar cell according to claim 1, characterized in that: The preparation method of the electron transport layer comprises: evaporating C60 on the perovskite layer to obtain electron transport; the thickness of the C60 is 20-50 nm, and the evaporation rate is 0.1-0.5 Å s -1 .
9. The method for preparing a wide bandgap perovskite solar cell according to claim 1, characterized in that: The preparation method of the electrode layer comprises: evaporating a gold electrode on the electron transport layer to obtain the electrode layer; the thickness of the gold electrode is 60-120 nm, and the evaporation rate is 1-5 Å s -1 .
10. A wide bandgap perovskite solar cell, characterized in that: The wide bandgap perovskite solar cell is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Cited By
Organic solar cell active layer taking dicyanoimidazole derivative as additive and preparation method and application thereof
CN122161329A